Shaping the conflict - Alan Finlay (Communicare)
Prior research suggests there is a lack of editorial-level policy thinking around HIV/AIDS coverage in South African media institutions. At the same time, constraints of time, capacity and resources, common in the commercial newsroom, mean it is often illequipped to deal more comprehensively with the complex effects of the pandemic in the country. A quantitative study, conducted as a sister study to this, shows the press took a strongly critical position in relation to the government health policy on anti-retrovirals (ARVs) during the monitored periods (March-May 2002 and March-May 2003). Given the relative complexity of a public ARV treatment programme, the lack of resources and capacity in the newsroom, as well as the lack of widespread editorial-level policy thinking on HIV/AIDS coverage, how is it that the press came to represent a position so strongly in opposition to the government policy? In the context of an overview of the quantitative findings, this paper explores several possible reasons that emerged during interviews conducted with key informants in the field of HIV/AIDS and the media.